The Framework of Customer Engagement on Customer Satisfaction : The Antecedents and Consequences - Titin Hargyatni; Kusna Djati Purnama; Danang Wiratnoko; Robby Andika Kusumajaya; Sri Handoko (Journal of Management and Informatics, 2022)
This study examines the relationship between requirements and framework development in Customer Engagement (CE). In this paper it is developed based on engagement theory with the assumption that satisfying relationships will be able to create emotional relationships so that colleagues will be involved and bound to each other. Based on theoretical studies, this paper proposes a framework that examines the components that exist in CE, antecedents. involved and the consequences of CE. To complete the study, we also discuss how the type of industry, company characteristics - Business to Business vs Business to Consumer - and value and level of involvement affect the satisfaction relationship, both direct and indirect contributions from the point of view of emotional involvement in Customer Engagement. Next, examine the development of Customer Engagement and how to maximize company performance by making appropriate strategic changes. The findings of this paper are the relationship between emotions and the indirect contribution of customers’ needs to be improved to the company's service industry with the B2B concept for products/services with a high level of involvement; Furthermore, it is also necessary to improve services for products or services with a high level of brand value and companies that provide a higher level of satisfaction.